Positive and Negative Affect Mediate the Influences of a Maladaptive Emotion Regulation Strategy on Sleep Quality - Latif, Iqra; Hughes, Alun T. L.; Bendall, Robert C. A. (Frontiers in Psychiatry, 2019)
Positive affect, negative affect, and emotion regulation strategies are related to sleep quality. Emotion regulation can also act as either a protective factor against the development of psychopathologies, or as a risk factor for their development, and therefore may be one mechanism linking mental health and sleep. However, currently it is not known whether affect can mediate the impact of emotion regulation strategy use on sleep quality. An opportunity sample in a healthy population completed the Positive and Negative Affect Schedule providing measures of positive and negative affect, the Pittsburgh Sleep Quality Index providing a measure of sleep quality, and the Emotion Regulation Questionnaire to record habitual use of emotion regulation strategies. Data were analysed using regression and mediation analyses. Negative affect and expressive suppression were positively correlated with PSQI score suggesting that as negative affect and expressive suppression use increased, sleep quality decreased. Positive affect was negatively correlated with PSQI score suggesting that as positive affect increased sleep quality improved. Further, mediation analyses revealed that both positive affect and negative affect mediated the impact of expressive suppression on sleep quality. Moreover, this partial mediation provides the first description that the influences of affect and expressive suppression on sleep quality are at least partially distinct. Targeting improvements in negative affect and effective emotion regulation strategy use may improve the efficacy of interventions aimed at improving sleep quality and the reduction in symptomology in psychopathologies.